Ordinance No. 160: An Ordinance Defining Offenses Against the Peace and Good Order of the City of Caldwell, and Providing Punishment Therefore, THE CALDWELL TRIBUNE, May 27, 1910, at 2 (Caldwell, Idaho) § 19 - (:unkn) unknown (General Publisher, 1910)
Prohibited discharging any firearms within city limits without sufficient breastworks or batter for the protection of the citizens. Violators fined not exceeding one hundred dollars.
--
Keywords: DISCHARGE